On the parasitoid wasps of the African tropical forest – and how their species richness compares to Amazonia - Hopkins, Tapani (fi=Turun yliopisto|en=University of Turku|, 2021)
Our planet is inhabited by an astounding diversity of species, most of which have not yet been discovered. This species richness is at its highest in the tropics and particularly in tropical insects. The tropical Darwin wasps (Hymenoptera: Ichneumonidae), which represent one of the largest animal families on Earth, are especially poorly known. So much so, that doubts persist as to their being species rich in the tropics. In this PhD, I collected Darwin wasps in tropical forest in Uganda, using large numbers of Malaise traps for a year. I then examined the species richness of one of the subfamilies (Rhyssinae), and also investigated the phenology and habitat use of the species. I compared the species richness of my Ugandan site with that of Amazonia, which had been sampled using the same methods. A year of Malaise trapping discovered six rhyssine species in Uganda. Two of these species were new to science. These results, together with the results of previous sampling at the site, clearly demonstrated that there is a diverse Darwin wasp fauna still awaiting discovery in Africa. Ugandan rhyssines were caught in largest numbers in dry weather, near decaying wood in primary forest. The results suggested they prey on wood-boring larvae, and also gave an indication of their adult lifespan. This kind of data is rarely obtained in the tropics, and I suggest applying the same methods to the results of other sampling programs. Comparing the rhyssines of two tropical forest sites on different continents suggested that the Amazonian site I compared to may have even more species than my African site. However, Amazonia did not stand out as anomalously diverse. I suggest collecting Darwin wasps from further sites using the same methods. This would answer the question of whether or not Darwin wasps are species rich throughout the tropics, with Amazonia being among the more diverse areas. Using large numbers of Malaise traps for a year gave a wealth of information on what species were present at a tropical site, how they lead their lives, and how they compare to their counterparts on another continent. Current work has only scratched the surface of the astounding diversity of tropical Darwin wasps.

Planeettaamme asuttavat miljoonat eliölajit, joista useimpia ei vielä ole löydetty. Tämä ällistyttävä lajirunsaus on korkeimmillaan tropiikissa, ja trooppiset hyönteiset muodostavat siitä suuren osan. Maailman kenties lajirikkain eläinheimo, ahmaspistiäiset (Hymenoptera: Ichneumonidae), tunnetaan erityisen huonosti tropiikissa. On jopa epäilty sen olevan poikkeuksellisen vähälajinen tropiikissa. Väitöskirjaani varten keräsin ahmaspistiäisiä vuoden ajan lukuisilla Malaisepyydyksillä Ugandan trooppisessa metsässä. Tarkastelin erään alaheimon (porapistiäiset, Rhyssinae) lajirunsautta, ja selvitin miten lajit jakautuvat eri metsätyyppeihin sekä milloin ne lentävät. Lisäksi vertasin lajirunsautta Amazonin sademetsään, jossa oli kerätty ahmaspistiäisiä samalla menetelmällä. Pyydykset saivat vuoden aikana saaliiksi kuusi porapistiäislajia. Näistä kaksi oli tieteelle uusia. Nämä tulokset (ja erään aiemman keräyksen tulokset) osoittavat että Afrikassa elää runsas ja suurelta osin tuntematon loispistiäislajisto. Porapistiäisiä saatiin Ugandassa eniten sateettomalla säällä, lahopuun lähellä koskemattomassa metsässä. Tämä viittaa siihen, että ne loisivat lahopuussa eläviä toukkia. Saimme myös viitteitä siitä, kuinka pitkään ne elävät aikuisena. Tropiikista saadaan harvoin tällaista tietoa, ja suosittelenkin menetelmieni käyttämistä myös muiden trooppisten pyydystysten yhteydessä. Verratessani kahta trooppista aluetta jotka sijaitsevat eri mantereilla sain viitteitä siitä, että vertailukohtana toimiva Amazonin sademetsän alue olisi afrikkalaista tutkimusaluettanikin lajirunsaampi. Kummatkin alueet vaikuttivat kuitenkin kuuluvan samaan lajirunsauden jatkumoon. Suosittelen vastaavaa pyydystystä useammalla tutkimusalueella. Näin selviäisi, ovatko ahmaspistiäiset lajirikkaita koko tropiikissa, ja onko Amazonin sademetsä lajirikkaammasta päästä. Keruumenetelmämme, jossa lukuisia Malaisepyydyksiä käytetään vuoden ajan, antoi runsaan aineiston. Se tuotti tietoa erään trooppisen metsän lajistosta, lajien elintavoista ja siitä miten ne vertautuvat toisen mantereen vastaaviin lajeihin. Olemme vasta pääsemässä alkuun tropiikin ällistyttävän monimuotoisten ahmaspistiäisten kartoittamisessa.